Determining in vivo elasticity and viscosity with dynamic Scheimpflug imaging analysis in keratoconic and healthy eyes. Issue 5 (11th January 2016) - Wang, Li‐Ke; Tian, Lei; Zheng, Yong‐Ping
Abstract : The paper presents a novel analysis method of corneal elasticity and viscosity based on corneal visualization Scheimpflug technology (CorVis ST) for keratoconus diagnosis. Methods for air puff force measurement and corneal imaging boundary extraction were proposed. Corneal biomechanical properties, described as tangent stiffness coefficient ( S TSC ) and energy absorbed area ( A absorbed ), were assessed using the curves of the applied air puff force with corneal displacement to form a loading‐unloading cycle. Twenty‐five patients with keratoconus and 34 healthy control subjects, matched for intraocular pressure (IOP), were enrolled in this prospective study. The results showed that the intraclass correlation coefficients (ICC) of the S TSC and A absorbed were 0.941 and 0.878 in Healthy group; and were 0.891 and 0.809 in Keratoconus group, respectively. Both S TSC and A absorbed of keratoconus patients were significantly different from that of controls (both probability value P < 0.001). ROC curve analysis showed that the area under curve for S TSC was 0.918 and for A absorbed was 0.894, which reached a good level of predictive accuracy for detecting keratoconus. Our results demonstrated that this new analysis method could be used to characterize the biomechanical properties of corneas.(a ) The air puff force of CorVis ST was measured by a custom‐designed force detection system. (b ) Corneal displacement was extracted from CorVis ST using a proposed imaging analysis. (c ) With the utilization of the air puff force and corneal dynamic displacement, an analysis method was developed to introduce new corneal biomechanical parameters – S TSC and A absorbed . Abstract : The paper shows a novel method of determining the corneal biomechanical properties. Combined with air puff force of CorVis ST and corneal displacement, which extracted from CorVis ST video using proposed imaging analysis, the S TSC and A absorbed were generated to represent the corneal elasticity and viscosity properties, respectively. In clinical studies, the S TSC and A absorbed metrics were statistically different in patients with keratoconus compared with those in healthy controls.